The reality of use of modern technology in the teaching of socialities in Al - Leith governorate and the obstacles to its use from the point of view of teachers and educational supervisors - Al-Zahrani, Iedah Mohammed attiah (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the degree of use of social parameters in the secondary stage of educational techniques in Al-Lith Governorate in Saudi Arabia and the constraints of its use from the point of view of teachers and educational supervisors. In order to achieve the objective of the study, the researcher used the descriptive method; she prepared a questionnaire; it was applied to a sample of purpose; it included all the educational supervisors of the social subjects, (2) educational supervisors and (8) teachers of social studies; In the secondary school of the first courses in al-lyth governorate.The results of the study showed that the use of social parameters for educational techniques in teaching obtained a general average (3.81) and a verbal evaluation (large). At the level of the three axes, the difficulties came first, with an average of 3.95, The availability of the devices is averaged (3.67), all with a verbal estimate (large). The results of the study showed that there were no statistically significant differences at the level of significance (α = 0.05) due to the variable of experience in the degree of use of social parameters of teaching techniques in teaching. In light of the results of the study, the researcher recommended holding training courses for social teachers on the use of educational techniques in teaching and enhancing their performance by social supervisors and school principals.
Keywords: reality of use; educational technologies; Social articles; High school; Laith Governorate